Delayed clearance of triglyceride‐rich lipoproteins in young, healthy obese subjects. Issue 5 (15th October 2015) - Larsen, M. A.; Goll, R.; Lekahl, S.; Moen, O. S.; Florholmen, J.
Summary: Obesity is associated with the metabolic syndrome. The aims were, first, to study the postprandial triglyceride clearance in young, healthy obese subjects and, second, to investigate if fasting triglycerides can predict delayed postprandial triglyceride clearance. Eighteen apparently healthy, obese subjects with no clinical signs of metabolic disturbances participated. Controls were age‐ and sex‐matched, healthy, normal weight subjects. Subclinical markers of metabolic disturbances were assessed by measuring postprandial triglycerides in serum and in chylomicrons by oral fat tolerance test. Postprandial triglyceride clearance for 8 h was assessed indirectly as removal of the lipid from serum during the oral fat tolerance test. Insulin resistance was measured by the homeostasis model assessment of insulin resistance (HOMA‐IR). Twelve (66%) of the apparently healthy obese individuals had insulin resistance measured by HOMA‐IR. There was a delayed clearance of serum triglycerides and chylomicron triglycerides at 6 h when compared with the control group, while, at 8 h, the differences were only detected for the chylomicron triglyceride clearance. Triglyceride response was significantly greater in the obese subjects. Fasting triglycerides in upper normal level predicted a delayed postprandial triglyceride clearance and insulin resistance. In young, apparently healthy obese subjects early metabolic disturbances including insulin resistance and delayed postprandial triglyceride clearance can be detected. Fasting serum triglyceride in upper normal level predicted delayed postprandial triglyceride clearance and insulin resistance.